Potassium Concentration on Admission Is an Independent Risk Factor for Target Lesion Revascularization in Acute Myocardial Infarction - Tsuyoshi Honda; Kazuteru Fujimoto; Yuji Miyao; Hidenobu Koga; Masanobu Ishii (The Scientific World Journal)
Background. Acute myocardial infarction (AMI) is accompanied by excessive production of catecholamines, which is characterized by a hypokalemic dip. A polymorphism of the adrenergic receptor has also been reported to be associated with target lesion revascularization (TLR) after coronary intervention. Subjects and Methods. We enrolled 276 consecutive patients with AMI within 24 hours of symptom onset, who underwent emergency coronary intervention using bare metal stents and had examinations over a 5–10-month follow-up period. The patients were divided into tertiles based on their serum potassium level on admission (low K, <3.9; mid K, ≥3.9, <4.3; and high K, ≥4.3). Results. Sixty-four TLRs were observed in the study. Increased potassium concentration was associated significantly with TLR. Patients in the high K group were about two and a half times more likely to have a TLR after AMI compared to those in the low K group. Multiple logistic analysis showed that potassium level on admission was an independent risk factor for TLR (odds ratio 1.69; confidence interval 1.04 to 2.74; P=0.036). Conclusions. These findings indicated that increased potassium levels on admission might predict TLRs in AMI patients treated with bare metal stents.